A P450 fusion library of heme domains from Rhodococcus jostii RHA1 and its evaluation for the biotransformation of drug molecules. Issue 17 (1st September 2015) - Kulig, Justyna K.; Spandolf, Claudia; Hyde, Ralph; Ruzzini, Antonio C.; Eltis, Lindsay D.; Grönberg, Gunnar; Hayes, Martin A.; Grogan, Gideon
Graphical abstract: Abstract: The actinomycete Rhodococcus jostii RHA1 contains a multitude of oxygenase enzymes, consonant with its remarkable activities in the catabolism of hydrophobic xenobiotic compounds. In the interests of identifying activities for the transformation of drug molecules, we have cloned genes encoding 23 cytochrome P450 heme domains from R. jostii and expressed them as fusions with the P450 reductase domain (RhfRED) of cytochrome P450Rhf from Rhodococcus sp. NCIMB 9784. Fifteen of the fusions were expressed in the soluble fraction of Escherichia coli Rosetta (DE3) cells. Strains expressing the fusions of RhfRED with genes ro 02604, ro 04667, ro 11069, ro 11320, ro 11277, ro 08984 and ro 04671 were challenged with 48 commercially available drugs revealing many different activities commensurate with P450-catalyzed hydroxylation and demethylation reactions. One recombinant strain, expressing the fusion of P450 gene ro 11069 (CYP257A1) with RhfRED, and named Ro07-RhfRED, catalyzed the N-demethylation of diltiazem and imipramine. This observation was in accord with previous reports of this enzyme's activity as a demethylase of alkaloid substrates. Ro07-RhfRED was purified and characterised, and applied in cell-free biotransformations of imipramine (7 μM) giving a 63% conversion to the N -desmethyl product.